2003
DOI: 10.1021/bi034562h
|View full text |Cite
|
Sign up to set email alerts
|

Electron Transfer in Flavocytochrome P450 BM3:  Kinetics of Flavin Reduction and Oxidation, the Role of Cysteine 999, and Relationships with Mammalian Cytochrome P450 Reductase

Abstract: Cys-999 is one component of a triad (Cys-999, Ser-830, and Asp-1044) located in the FAD domain of flavocytochrome P450 BM3 that is almost entirely conserved throughout the diflavin reductase family of enzymes. The role of Cys-999 has been studied by steady-state kinetics, stopped-flow spectroscopy, and potentiometry. The C999A mutants of BM3 reductase (containing both FAD and FMN cofactors) and the isolated FAD domain are substantially compromised in their capacity to reduce artificial electron acceptors in st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
66
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(76 citation statements)
references
References 35 publications
10
66
0
Order By: Relevance
“…SDS-PAGE (15%) indicated that the proteins were pure. The concentration of purified proteins was measured spectrophotometrically using molar extinction coefficients 11,300 M Ϫ1 cm Ϫ1 for the FAD domains and 21,200 M Ϫ1 cm Ϫ1 for the reductase domains, as described previously (7,31,32).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…SDS-PAGE (15%) indicated that the proteins were pure. The concentration of purified proteins was measured spectrophotometrically using molar extinction coefficients 11,300 M Ϫ1 cm Ϫ1 for the FAD domains and 21,200 M Ϫ1 cm Ϫ1 for the reductase domains, as described previously (7,31,32).…”
Section: Methodsmentioning
confidence: 99%
“…Absorption transients from the stopped-flow experiments were fitted to appropriate exponential functions using Spectrakinetics software (Applied Photophysics). Observed rate constants for flavin reduction by NADH showed a hyperbolic dependence on coenzyme concentration, and data were fitted to Equation 1 (31) to determine the apparent enzyme-coenzyme dissociation constant, K, and the limiting rate of hydride transfer (k lim ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These residues are represented in rat nNOS by Asp-1393, Ser-1176, and Cys-1349 (27). Mutagenic substitution studies on the analogously positioned residues in FNR enzymes, cytochrome P450 reductase, and other related enzymes have established that each of the three residues helps to enhance the rate of hydride transfer between NAD(P)H and FAD (32)(33)(34)(35)(36)(37)(38)(39)(40). Given the structural and regulatory properties of the NOSs, we sought to examine how one of these conserved residues (Asp-1393, Fig.…”
Section: Nitric Oxide (No)mentioning
confidence: 99%